“BEHAVIOR OF SKELETAL STEEL REINFORCE LIGHT WEIGHT FERROCEMENT BEAMS UNDER MONOTONIC AND REPEATED FLEXURAL LOADING - G.M, Naveen; Suresh, Dr. G.S. (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
Light weight ferrocement is a composite material consisting of cement-sand mortar (matrix) along with light weight fine aggregate ( In this research blast furnace slag is employed as light weight fine aggregate ) as a replacement of sand in some quantity reinforced with layers of small diameter wire meshes and closely spaced small-diameter steel rods. The present work is concentrated on two major aspects, (i) Effect of blast furnace slag on ultimate strength and (ii) Behavior of light weight ferrocement element under flexural loading. The first part of the present study has been focused on the effect of blast furnace slag(BFS) on ultimate strength with replacement of slag by 0%,10%,20%&30% and second part of the work focusing the behavior of light weight ferrocement beam under monotonic & repeated loads with increased load. The results obtained from this work is expected to be useful in determining the first crack strength and ultimate strength of light weight ferrocement beams subjected to similar types of forces and thus will help toward designing ferrocement elements to withstand monotonic and repeated flexural loading.